PELAKSANAAN PEMBELAJARAN OLEH GURU KELAS II BAGI ANAK AUTIS DI SDN. 31 PAYAKUMBUH - Resti - Indra (Universitas Negeri Padang, 2014)
The aim of this research is to looking the learning realization by teacher class II to autism student. With approach of descriptive-qualitative with technique observation, interview, and documentation study it will be discuss about planning, realization, and marking with the design of learning program by class teacher to autism student in SDN. 31 Payakumbuh. Based on research product , we can take inference that nothing special program posting by the teacher to autism student because is nothing difference between other student.